Waqf lands and challenges from the legal perspectives in Malaysia - Mohamad, Nor Asiah; Syed Abdul Kader, Sharifah Zubaidah; Ali, Zuraidah (2012)
This paper seeks to look at waqf administration in Peninsular Malaysia from the perspective of enforcement of the law. ‘Waqf’ is listed under the State List of the Federal Constitution 1957 and thus comes under the jurisdiction of the state governments. Given the multifarious backgrounds of the states and religions in Malaysia, the question is how far does the administration of waqf lands achieve some semblance of uniformity and whether waqf lands are able to realize its role to be able to endow maximum benefits to the Muslim ummah as a whole and specifically those named as beneficiaries? The issue often raised in academic and non-academic discourses on waqf lands in Malaysia is that the legal provisions specifically the National Land Code 1965, is not able to strictly guarantee the protection accorded to waqf lands according to that which is required by the teachings of Islam. The lack of understanding of legal practitioners and the legal draftsmen of yore which began from the times of British influence resulted in the lack of specific legal provisions for the administration of waqf lands in Malaysia. Today, the same legal challenge permeates amongst waqf administrators as well as land administrators who also have minimal appreciation concerning the spirit and rationale of waqf in Islam. This paper puts forth two proposals – one in the short term and one in the long term. In the short term, all waqf administration is to be streamlined and a specific procedure is to be identified and put in place having regard to the existing legal framework that involves the state administration, the Attorney-General’s Chambers, the Ministry related to Lands and Mines as well as the judiciary. In the long term, amendments of the laws are imminent so that the status and objectives of waqf could be realized in the way that it is prescribed by Islam.